Cerebral abcess of dental origin about a case in the Department of Stomatology Maxillofacial Surgery of University Hospital Center Yalgado Ouedraogo - Sanfo Mahamadi; Millogo Mathieu; Coulibaly Arsène; Idani Motandi; Dargani Michel Fabien (Elsevier, 2022)
Diffuse cervico-facial cellulitis of dental origin is a serious, potentially fatal condition that may be responsible for focal affections or distant infections. We report a case of intracerebral suppuration following a diffuse cellulitis of dental origin in a recently delivered woman. Observation: It was a 30-year-old housewife living in a rural area of Burkina Faso, was seen at 10 days postpartum of a stillborn child for inflammatory swelling of the left hemiface following odontalgia that had been evolving for more than 2 weeks. Clinical and paraclinical examinations led to the diagnosis of diffuse cervicofacial cellulitis. The patient received probabilistic antibiotic therapy and surgical drainage of the facial suppuration under local anesthesia. The evolution was marked by the appearance of signs of cerebral localization and the cerebral CT scan performed found a homolateral left temporal brain abscess. The patient was referred to neurosurgery for further treatment and died a few days after leaving the hospital against medical advice for lack of financial means. Conclusion: Focal cerebral infections of dental origin are serious and fatal. Only prevention could improve their prognosis.